THE PROBLEM OF ADEQUACY AND APPLICABILITY OF THE SYSTEM OF PSYCHOLOGICAL ASSESSMENT OF HUMAN CAPITAL - Avanesyan, H.M. (Modern Psychology, 2019)
The article analyzes the main approaches to the concept of human capital and the role of the psychological component in it. The use of a universal algorithm will make it possible to identify criteria for the interpretation of substantive elements and assessment of the psychological components of human capital. It was assumed that the transition from the assessment system in the management of human resources, its modification, to the psychological assessment of human capital will expand the functionality of the effective use of investments and economic resources. The results of our many years of research and practical work on the introduction of psychological diagnostic methods for selecting personnel in state and non-state organizations, educational institutions and sports teams are succinctly presented. The problem of developing a universal and adequate system of psychological assessment of human capital is of particular relevance for countries at the stage of reforming the political and economic structure.
Keywords: human capital; human resources; psychological evaluation; scope of activities; the economy and investments